Implementing a whole-school relationships and sex education intervention to prevent dating and relationship violence: evidence from a pilot trial in English secondary schools. Issue 6 (1st November 2020) - Meiksin, Rebecca; Campbell, Rona; Crichton, Joanna; Morgan, Gemma S.; Williams, Pippa; Willmott, Micky; Tilouche, Nerissa; Ponsford, Ruth; Barter, Christine A.; Sweeting, Helen; Taylor, Bruce; Young, Honor; et al.
ABSTRACT: Adolescent dating and relationship violence is associated with health harms and is an important topic for sex education. School-based interventions addressing this have been effective in the USA, but schools in England confront pressures that might hinder implementation. We assessed the feasibility of, and contextual enablers/barriers to implementing Project Respect, a whole-school intervention. We conducted a pilot trial with process evaluation in six English secondary schools. Intervention comprised: training; policy-review; mapping and patrolling 'hotspots'; parent information; help-seeking app; and a curriculum (including student-led campaigns) targeting dating violence. Process evaluation included assessments of fidelity and interviews with the trainer and school staff. Schools delivered training and lessons partially or completely and made parent and app information available. Two schools conducted policy reviews; none patrolled hotspots or implemented campaigns. Implementation was strengthened where staff saw dating violence as a priority. Delivery was undermined where staff were insufficiently involved, lacked time for planning or struggled to timetable lessons, and where new school challenges undermined engagement. School-based health interventions must work to build staff buy-in and ensure they do not overburden schools. Dating and relationship violence might best be addressed in this context as a broader aspect of sex education.